Agmatine inhibited tolerance to and dependence on morphine in guinea pig ileum in vitro - Li Jin; Li Xin; Pei Gang; Qin Bo-Yi (Acta Pharmacologica Sinica, 2016)
AIM: To observe effect of agmatine (Agm) on tolerance to and substance dependence on morphine (Mor) in guinea pig ileum longitudinal muscle (GPILM). METHODS: The experiment was performed in electric field stimulation (EFS) test in vitro. RESULTS: Mor inhibited twitch contractions of GPILM induced by EFS [IC50 = 140 (107-182) nmol.L-1]. Incubation of GPILM with Mor 270 nmol.L-1 for 8 h evoked a 37-fold increase in IC50 of Mor (tolerance) and a contractile response to naloxone (Nal, substance dependence). When the preparations were coincubated with Mor + Nal and Mor + Agm, Mor lost the ability to induce tolerance and inhibited the contractile responses of the preparations to Nal by 90% and 75%, respectively. These effects of Agm could be almost completely antagonized by idazoxan. CONCLUSION: Agm prevented the development of tolerance to and substance dependence on Mor in GPILM in vitro by activation of imidazoline receptors.